2024
DOI: 10.1063/5.0168564
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of thermoelectric and magnetotransport properties of single crystalline Bi2Se3 topological insulator

Pintu Singha,
Subarna Das,
Nabakumar Rana
et al.

Abstract: The realization of remarkable thermoelectric (TE) properties in a novel single-crystalline quantum material is a topic of prime interest in the field of thermoelectricity. It necessitates a proper understanding of transport properties under magnetic field and magnetic properties at low field. We report polarized Raman spectroscopic study, TE properties, and magneto-resistance (MR) along with magnetic characterization of single-crystalline Bi2Se3. Polarized Raman spectrum confirms the strong polarization effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In 3D TIs, the thermoelectric properties of surface states have been extensively investigated [34][35][36][37][38][39][40][41][42][43]. In experiment, Sun et al found that the thermoelectric figure of merit(ZT) of Bi 2 Se 3 can be enhanced by reducing the grain size of bulk due to increased topologically conducting surfaces [44].…”
Section: Introductionmentioning
confidence: 99%
“…In 3D TIs, the thermoelectric properties of surface states have been extensively investigated [34][35][36][37][38][39][40][41][42][43]. In experiment, Sun et al found that the thermoelectric figure of merit(ZT) of Bi 2 Se 3 can be enhanced by reducing the grain size of bulk due to increased topologically conducting surfaces [44].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely acknowledged that Bi 2 Te 3 , belonging to V 2 VI 3 type chalcogenide family (V = Bi, Sb; VI = Te, Se, S) is a promising TE material around room temperature [13]. Soft chemical bonding, low sound velocities due to heavy constituent elements, large unit cell, narrow bandgaps, high carrier mobilities and strong anharmonic interactions together result in its exceptionally high TE performance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%